Beyond the label: real-world gastrointestinal adverse events associated with vedolizumab – a decade of FAERS pharmacovigilance - Zheng, Jianhong; Qiu, Chunfeng; Zhang, Zhen (Frontiers in Pharmacology, 2026)
BackgroundVedolizumab is a gut-selective biologic widely used for inflammatory bowel disease (IBD). While randomized controlled trials (RCTs) provide initial safety profiles, real-world pharmacovigilance data are crucial for identifying a broader spectrum of adverse events (AEs), including rare or underrecognized associations. This study aimed to comprehensively characterize the real-world reporting frequency and characteristics of gastrointestinal AEs associated with vedolizumab using spontaneous reporting data.MethodsWe analyzed 59,976 vedolizumab-related individual case safety reports from the U.S. Food and Drug Administration Adverse Event Reporting System (FAERS) database, covering the period from Q1 2014 to Q4 2024. After meticulous exclusion of IBD diagnostic terms, 17,943 mentions of vedolizumab-associated gastrointestinal AEs were included. Disproportionality analysis, employing reporting odds ratios (ROR) with a threshold of ≥20 cases and a 95% confidence interval lower bound >1, was performed to detect significant signals. Descriptive analyses, time-to-onset (TTO) analysis, and a semi-quantitative clinical relevance assessment system were also utilized.ResultsDisproportionality analysis identified 95 significant gastrointestinal AE preferred terms (PTs). Common and strongly signaled events included diarrhea, abdominal pain, haematochezia, and frequent bowel movements. Notably, 70 of these 95 significant PTs (73.7%) are not explicitly listed in the current vedolizumab drug label, suggesting potential novel or underrecognized associations. Most reported AEs were serious (90.09%). Analysis of demographic data revealed significant differences in the proportion of serious reports across gender, weight, and age groups. Males (91.44%) and patients in the <50 kg group (87.30%) had higher proportions of serious reports. Notably, adult patients (18∼65 years) showed a higher proportion of serious outcomes compared to pediatric and elderly groups, although this finding may be influenced by data completeness bias. The median time-to-onset for gastrointestinal AEs was 190 days.ConclusionThis comprehensive real-world FAERS analysis identifies both known and a substantial number of previously underrecognized gastrointestinal AEs associated with vedolizumab. The high proportion of serious events, particularly observed in male patients and those with lower body weight, underscores the need for enhanced clinical vigilance and targeted monitoring, especially early in the treatment course. These hypothesis-generating findings warrant further validation through dedicated clinical studies.